2015
DOI: 10.1371/journal.pone.0137200
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Reduce Inflammation in Antiretroviral Treated, HIV-Infected Individuals: Results of the “Probio-HIV” Clinical Trial

Abstract: BackgroundHIV infection results in damage to the gastrointestinal (GI) tract, microbial translocation and immune activation. These are not completely normalized with combined antiretroviral therapy (cART). Moreover, increate morbidity and mortality of cART-treated HIV-infected individuals is associated with inflammation.MethodsIn order to enhance GI tract immunity, we recruited and treated 20 HIV-infected humans with cART supplemented with probiotics and followed inflammation and immunological parameters (clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
0
3

Year Published

2016
2016
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 33 publications
6
91
0
3
Order By: Relevance
“…In a recent study, intake of a probiotic containing several Lactobacillus, Bifidobacterium , and Streptococcus spp. significantly reduced CD4+ and CD8+ T cell activation and plasma concentrations of high-sensitivity C-reactive protein, a biomarker associated with cardiovascular disease risk, in ART treated HIV-infected adults [102**]. Interestingly, these patients also reported fewer episodes of diarrhea and constipation.…”
Section: Therapeutic Approaches To Improve Microbiome and Microbial Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, intake of a probiotic containing several Lactobacillus, Bifidobacterium , and Streptococcus spp. significantly reduced CD4+ and CD8+ T cell activation and plasma concentrations of high-sensitivity C-reactive protein, a biomarker associated with cardiovascular disease risk, in ART treated HIV-infected adults [102**]. Interestingly, these patients also reported fewer episodes of diarrhea and constipation.…”
Section: Therapeutic Approaches To Improve Microbiome and Microbial Tmentioning
confidence: 99%
“…Interestingly, these patients also reported fewer episodes of diarrhea and constipation. However, plasma concentrations of sCD14, a biomarker of MT, did not decrease after sustained probiotic intake [102**]. Another study demonstrated that intake of a probiotic yeast, Saccharomyces boulardii , reduced plasma concentrations of LBP and IL-6 in ART-treated HIV-infected individuals [103*].…”
Section: Therapeutic Approaches To Improve Microbiome and Microbial Tmentioning
confidence: 99%
“…In HIV-infected individuals, probiotics have been shown to decrease inflammation and microbial translocation (17,18). Thus, replenishing the gut microbiome with beneficial commensals may improve immunity, decrease inflammation, and improve health in individuals with HIV infection.…”
mentioning
confidence: 99%
“…These results are in accordance with a study carried out by d'Ettorre et al in 2015, where HIV infected patients on ART have been supplemented with probiotics for 48 weeks. In the treatment group, it has been observed a significant reduction in the levels of immune activation on CD4 + and CD8 + T lymphocytes for both markers CD38 and HLA-DR, and of their simultaneous expression, and lower microbial products, LPS and C-reactive protein plasma levels, with values comparable to control group (HIV seronegative subjects) [23]. Thus, in HIV infected subjects, the Lactobacillus casei Shirota would be beneficial immunologically, virologically, and bacteriologically.…”
Section: Probiotics As a New Therapeutic Approach That Might Improve mentioning
confidence: 93%